Integrating Virtual Laboratories in Chemistry Education: Vocational Students’ Responses to Cation Qualitative Analysis - Samosir, Rafidah Almira; Ardila, Mutia; Pratiwi, Alfira Julian; Kurniawan, Ekin Dwi Arif; Ridho, Dimas (Universitas Pendidikan Mandalika, 2025)
Research on student responses and the challenges of implementing virtual laboratories in qualitative cation analysis practicums within vocational pharmacy education remains limited. This study aims to explore student responses to the use of virtual laboratories as an alternative learning tool and to identify the challenges faced during its implementation. A qualitative approach with a case study method was employed. Data were collected through questionnaires and classroom observations during the learning process. The participants were 41 Grade XII students of the Pharmacy Program at SMK Galang Insan Mandiri Binjai, who engaged in virtual laboratory-based learning for qualitative cation analysis. The results indicate that virtual laboratories enhance student engagement and comprehension of the subject matter. Students responded positively to the use of virtual labs, reporting increased motivation and interest in developing technology-related skills. However, challenges such as limited digital literacy and infrastructure issues were also identified. The study suggests that virtual laboratories should be complemented with hands-on practicum sessions to provide a balanced and realistic learning experience. These findings offer valuable insights into the potential and limitations of virtual laboratory implementation in vocational pharmacy education.